Giair phương trình :
\(1) \sqrt{3x-2} + \sqrt{x-1} = 3 \)
\( 2) 3\sqrt{x+34} - 3\sqrt{x-3} = 1 \)
\( 3) 3x - 7\sqrt{x} +4 = 0 \)
\( 4) \frac{ \sqrt{x} -2 }{ \sqrt{x} -4 } =\frac{ 6 -\sqrt{x} }{7-\sqrt{x}} \)
\( 5) \frac{1}{2} \sqrt{x-1} -\frac{9}{2} \sqrt{x-1} + 3\sqrt{x-1} =-17\)
1) Đk: x \(\ge\)1
Ta có: \(\sqrt{3x-2}+\sqrt{x-1}=3\)
<=> \(3x-2+x-1+2\sqrt{\left(3x-2\right)\left(x-1\right)}=9\)
<=> \(2\sqrt{\left(3x-2\right)\left(x-1\right)}=12-4x\)
<=> \(\sqrt{3x^2-5x+2}=6-2x\)(\(1\le x\le3\))
<=> \(3x^2-5x+2=4x^2-24x+36\)
<=> \(x^2-19x+34=0\)
<=> \(x^2-17x-2x+34=0\)
<=> \(\left(x-17\right)\left(x-2\right)=0\)
<=> \(\orbr{\begin{cases}x=17\left(ktm\right)\\x=2\left(tm\right)\end{cases}}\)
Vậy S = {2}
3.Đk: x \(\ge\)0
\(3x-7\sqrt{x}+4=0\)
<=> \(3x-3\sqrt{x}-4\sqrt{x}+4=0\)
<=> \(\left(3\sqrt{x}-4\right)\left(\sqrt{x}-1\right)=0\)
<=> \(\orbr{\begin{cases}x=\frac{16}{9}\\x=1\end{cases}}\left(tm\right)\)
4. Đk: x \(\ge\)0; x \(\ne\)16; x \(\ne\)49
Ta có: \(\frac{\sqrt{x}-2}{\sqrt{x}-4}=\frac{6-\sqrt{x}}{7-\sqrt{x}}\)
=> \(\left(\sqrt{x}-2\right)\left(\sqrt{x}-7\right)=\left(\sqrt{x}-4\right)\left(\sqrt{x}-6\right)\)
<=> \(x-9\sqrt{x}+14=x-10\sqrt{x}+24\)
<=> \(\sqrt{x}=10\) <=> x = 100 (tm)
5.Đk: x \(\ge\)1
\(\frac{1}{2}\sqrt{x-1}-\frac{9}{2}\sqrt{x-1}+3\sqrt{x-1}=-17\)
<=> \(-\sqrt{x-1}=-17\) <=> \(x-1=17\) <=> x = 18 (tm)